Pelatihan produksi roti gandum sebagai pangan fungsional di Gampong Kajhu Kabupaten Aceh Besar (Training on wheat bread production as a functional food in Kajhu Village, Aceh Besar District) - Suryawati, S; Maysarah, Hilda; Nauval, Iflan; Safuni, Nani; Nova, Vera; Husna, Fauzul; Firdausa, Sarah; Suardi, Hijra Novia (Buletin Pengabdian, 2021)
The purpose of this activity was to train community members in Kajhu Village, Aceh Besar District to produce wheat bread with the addition of pumpkin. These community service activities were carried out in several stages which were socialization of the importance of a healthy lifestyle through focus group discussions by 3 experts in health field (clinical pharmacology, internal medicine, and clinical nutrition) and discussions about production, packaging, and product marketing. The result showed that 60 packs of bread with approximately 80 calories were produced every production time. Marketing and transaction (ordering) of products utilized online media. The sales value for 60 breads per day was Rp.420,000, with a profit of Rp. 180,000. This result was a good thing for Kajhu Village community group members because it could increase household income.In conclusion, the implementation of this product-based community service program has resulted in bread products with nutritious ingredients of wheat and pumpkin which have been clinically and experimentally (in other researches) proven to have anti-diabetic properties.